Psychosocial interventions reduce cortisol in breast cancer patients: systematic review and meta-analysis - Mészáros Crow, Edith; López-Gigosos, Rosa María; Mariscal-López, Eloísa; Agredano-Sánchez, Marina; García-Casares, Natalia; Mariscal-Larrubia, Alberto; Gutiérrez-Bedmar, Mario (Frontiers Media, 2023)
Introduction: Cancer initiation, progression and recurrence are intricate mechanisms that depend on various components: genetic, psychophysiological, or environmental. Exposure to chronic stress includes fear of recurrence that can affect biological processes that regulate immune and endocrine systems, increase cancer risk, and influence the survival rate. Previous studies show that psychological interventions might influence the level of cortisol that has been extensively used as a biomarker for measuring hypothalamic-pituitary-adrenal axis functioning and body's immunity response. This meta-analysis aimed to provide a quantitative scrutiny of the effect of certain types of psychosocial interventions on cortisol as a neuroendocrine biomarker in saliva or blood and might predict breast cancer (BC) progression. Methods: A literature search was performed in the following databases: PubMed, The Cohrane Library, Scopus, WOS, PsychInfo, Google Scholar, Ovid Science Direct. After methodical selection of originally generated 2.021 studies, the search yielded eight articles that met inclusion criteria. All these studies explored effects of psychosocial interventions that measured cortisol in total of 366 participants with BC, stages 0-IV, in randomized control trial or quasi experimental study design setting. We applied random effects model to conduct meta-analyses on the parameters of salivary and plasma cortisol and used PRISMA Guidelines as validated methodology of investigation to report the results. Results: Eight studies selected for meta-analysis have shown the reduction of cortisol level due to applied psychosocial intervention. The random effects model showed that interventions produced large effect sizes in reductions of cortisol in blood (Cohen's d = −1.82, 95% Confidence Interval (CI): −3.03, −0.60) and slightly less in saliva (d = −1.73, 95%CI: −2.68, −0.78) with an overall effect of d = −1.76 (95%CI: −2.46, −1.07).
Keywords: Mamas - Cáncer - Aspectos psicológicos; Psychosocial interventions; Cortisol; Breast cancer; Recurrence; Meta-analysis